Analisis Uji Validitas E-Job Sheet Praktikum Rangkaian Listrik di Jurusan Teknik Elektro - Dwi Annisa; Riki Mukhaiyar (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Practice learning during the Covid-19 pandemic was disrupted, causing the Department of Electrical Engineering, Padang State University to apply to learn using the blended learning method. This makes it difficult for students to carry out practicum in the laboratory because students are still confused. To overcome this, a learning media has been made in the form of an e-job sheet (e-job sheet) for electric circuit practicum courses. However, the e-job sheet that has been made has not been tested for feasibility. So this study aims to analyze the validity of the e-job sheet learning media for the Electrical Circuit Practicum course at the Department of Electrical Engineering, Padang State University. The research was conducted using a quantitative approach. The research subjects were E-Job Sheets and the respondents in this study were two media expert lecturers at the Department of Electrical Engineering, Padang State University. Data collection techniques using the questionnaire method. The research instrument used was a validated questionnaire. The questionnaire was then given to the respondents. The data was processed by quantitative statistical analysis techniques. This research produces a learning media product in the form of an e-job sheet with a very feasible category. So, it can be locked that the e-job sheet produced is valid so that it is suitable for use as a learning medium in the electrical circuit practicum course at the Department of Electrical Engineering, Padang State University.